The Implementation of the Somatic, Auditory, Visualization, and Intellectual Learning Model to Enhance Students’ Learning Creativity - Sodatul Hayati; Siti Zulaikhah; Era Octafiona (STAI Serdang Lubuk Pakam, 2025)
The low level of student learning creativity in Islamic Religious Education, particularly in Al-Qur'an and Hadith materials, remains a challenge at the junior high school level. This is due to the dominance of learning methods that do not optimally involve the physical, sensory, and intellectual aspects of students. Therefore, this study aims to examine the application of the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model in improving student learning creativity in Islamic Religious Education at SMP Negeri 1 Bandar Negeri Semuong, Tanggamus. This study used a quasi-experimental design with pre-test and post-test measurements to assess changes in student creativity. Data were collected through surveys, observations, and interviews with students and teachers. The results showed that the application of the SAVI model significantly increased student learning creativity, as reflected in the increase in pre-test and post-test scores, as well as increased student participation and involvement in the learning process. These findings confirm that interactive and multimodal learning approaches are effective in Islamic religious education. The implications of this study indicate that the SAVI model can be used as a strategic alternative in the development of creative, contextual, and relevant Islamic religious education that meets the demands of 21st-century education.